Aplicación del régimen aduanero de admisión temporal para perfeccionamiento activo y su incidencia en el desarrollo de las PYMES exportadoras del Ecuador - Chonillo Chavarría, Ana Belén (2022)
In Ecuador, in 2020, SME companies had a high development, with economic growth that helped improve the country's trade balance, especially those companies that exported their merchandise. There are many regimes, but, one must be considered and that makes a difference with others that are in the market, the temporary admission regime for inward processing allows the entry of products or goods from the Ecuadorian customs territory, with suspension of payments to import duties and taxes, resulting in a compensating product with the sole objective of exporting it, complying with what is determined by the regime. The objective of the following investigation is to carry out an analysis of the application of the temporary admission customs regime for active improvement in the exporting SMEs of Ecuador. The methodology applied in the present work allows a critical analysis through documentary and descriptive research, with a quantitative approach establishing a subjective selection of its indicators, it is documentary research and for this reason it does not present a sample. In this way, it is desired to motivate new SMEs to apply the temporary admission regime for active improvement, in order for new companies to appear that generate income. In this way, it is about evidencing with the understanding of the regime a correct application to better manage commercial activities at an international level, and to propose the use and application of the temporary admission regime for active improvement in many more companies.